The Role of Sport Television Media in Reducing Violence in Sports Institutions in Iraq - Fadhil Mosleh, Mohammed; Sadiq Ahmed, Mohammed; JarAllah Abudallah, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The communication revolution primarily contributes to distinguishing the role of media in reducing the phenomenon of violent and odd behavior in different areas of sport. Some new biased sports media issue a great rallying call for violent and aggressive behaviors in sports. The present study aims to investigate the role of sports media in the phenomenon of violence and hooliganism in Iraqi sports institutions. The research sample includes a random selection of 200 academic sports colleges in Iraqi universities. The pilot study was carried out with 40 staff members between 20 October 2019 and 17 November 2019, followed by the main experiment, which involved 160 staff members during the period from 8 December 2019 to 29 January 2020. An experimental method using a questionnaire with a descriptive method was adopted to collect the data. The data were statistically treated using the SPSS program. The obtained results show that there is a significant role for sports media in introducing sports programs in objective and neutral ways by spreading sports awareness and rejecting the phenomenon of violence and hooliganism in Iraqi sports institutions and society. Finally, the researchers highly recommend adopting interviews with sports experts and academics in order to show a unified message and send positive messages to the audience about good behavior in sports institutions.